The Significance of Didacticsi in Preparing Students to Teach EFL - Imen Aggoun (The Journal of Studies in Language, Culture and Society)
The present paper is a study of a hundred and fifty one (151) undergraduate students, focused on inferring the significance and effectiveness of studying didactics and assessing students’ background about the teaching profession. It also seeks to show an evaluation of the readiness and capacities of Master degree students, since many researchers claimed that the study of didactics is useless inside classrooms, and that most teachers rely upon their creativity and self-abilities in teaching rather than theories of teaching and learning. The research methodology adopted in this study is a descriptive one. It intended to describe two main variables: Didactics and student’s preparation to become EFL teachers. Data had been gathered through a series of questionnaires, administered to a sample of 151 participants and other questionnaire had been delivered to 04 teachers at the English department, Khenchela University. Finally, the results which had been obtained from this study showed that students gained a sufficient amount of knowledge which may serve them well in their teaching career; they consider themselves ready and capable to teach the moment they graduate.